Rancang Bangun Toko Perlengkapan Olahraga Berbasis Web - Prayogi, Aldi; Handika, Dian; Perdani, Nofri (Himpunan Dosen Gemilang Indonesia (HDGI), 2023)
Alphaware is an online shop that operates in the field of shoes such as sports shoes, fashion shoes and others. This shop was created with the aim of facilitating buying and selling access with customers because the process is fast and easy. Because of this, an accurate system is needed to predict the number of pieces of furniture. This information system applies the waterfall model in its development and is built with the PHP programming language and uses MYSQL. The design of e-commerce in this shop is made using a website, however, making this website allows for certain weaknesses, whether it lies in the transaction process or something else. By using this method, several problems still occur, including the very limited scope of the marketing process and a lack of customer interest due to the price being quite expensive even though the quality of the product corresponds to buying shoes at the Alphaware Store. Customers need a lot of time, effort and money to buy these shoes. The e-commerce that was built can process data on sales of shoe orders. This web-based e-commerce was built using the PHP programming.